Naskah Tafsir Al-Maraghi : (Studi Deskriptif Pada Kitab Tafsir Ahmad Mustofa AL-Maraghi) - Misnawati Misnawati; Maulida Putri Maulida Putri (Sekolah Tinggi Ilmu Al-Quran dan Sains Al-Ishlah, 2026)
The Tafsir Al-Margh is a high-quality interpretation, as can be seen from the interpretation methods and writing systematics used by its author. This study aims to analyze the text of Tafsir Al-Margh by examining the methods, patterns, and systematic approaches employed. The research findings indicate that Al-Margh's interpretative style is social literary, utilizing a bi al-ra’yi approach and leaning towards analytical methods. The systematic interpretation begins with presenting verses at the beginning of the discussion, typically only one or two verses related to the same meaning and purpose, followed by an explanation of vocabulary and terms to aid the reader’s understanding of difficult words. It also provides a general explanation of the verse's meaning, so that readers are not confused before grasping deeper meanings. Thus, readers can first recognize the general meaning of the verses.